2013
DOI: 10.2320/matertrans.m2012425
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness Evaluation of Thin Fe–Al Intermetallic Compound Layer at Reactive Interface between Dissimilar Metals

Abstract: The fracture toughness of FeAl intermetallic compounds (IMCs), FeAl and Fe 2 Al 5 , that form as a thin layer on steel substrate was investigated. A model for evaluating the fracture toughness of a brittle thin layer on an elastoplastic substrate was applied, and the fracture toughness was evaluated from the thickness of the IMC layer and the crack interval in the IMC layer after uniaxial tensile testing. The phase and microstructure of the IMC layer were varied to investigate their effects on the fracture tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is well known that the thickness of the IMC is a decisive factor for the strength of very dissimilar welds (e.g. Al/steel) [13, 25] and micro-electronic solder joints [26, 27]. It is reported that the thickness of IMC can affect both the fracture path and inherent strength/toughness of the IMC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the thickness of the IMC is a decisive factor for the strength of very dissimilar welds (e.g. Al/steel) [13, 25] and micro-electronic solder joints [26, 27]. It is reported that the thickness of IMC can affect both the fracture path and inherent strength/toughness of the IMC.…”
Section: Resultsmentioning
confidence: 99%
“…The thicker IMCs contain more microscopic flaws and defects, limiting the strength/toughness of the IMC [26]. In the case of Al-Fe IMCs, it is shown experimentally that an increase in the IMC thickness decreases the fracture toughness of the IMC layer [25]. Moreover, it is demonstrated by finite element modelling that the stress intensity factor at the edge of IMC increases by increasing the IMC thickness [27].…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Attentions have been increasingly given to further enhance the comprehensive properties of intermetallic composites and promote their industrial applications. [5][6][7] Few works have been reported for materials related to NiMo/ Mo 2 Ni 3 Si intermetallic composite, although there have been already tremendous efforts made on refractory metal based alloys. 8,9) The current problem for application of such alloys mainly lies in the lack of room temperature toughness.…”
Section: Introductionmentioning
confidence: 99%
“…They found that as the width of the Fe2Al5 phase decreased, the shear strength substantially increase [14]. Kyokuta et al showed that refining the Fe2Al5 phase increased the crack interval and the increase in crack interval correlates to an increase in fracture toughness for the finer grained Fe2Al5 [15]. Grain refinement within the IMC layer is a large factor in increasing the tensile shear strength of the component.…”
Section: Effect Of Alloying Elementsmentioning
confidence: 99%